Production of nitric oxide by murine macrophages induced by lipophosphoglycan of Leishmania major - Kavoosi, Gholamreza (The Korean Society for Parasitology, 2006)
Protozoan parasites of the genus Leishmania cause a number of important human diseases. One of the key determinants of parasite infectivity and survival is the surface glycoconjugate lipophosphoglycan (LPG). In addition, LPG is shown to be useful as a transmission blocking vaccine. Since culture supernatant of parasite promastigotes is a good source of LPG, we made attempts to characterize functions of the culture supernatant, and membrane LPG isolated from metacyclic promastigotes of Leishmania major. The purification scheme included anion-exchange chromatography, hydrophobic interaction chromatography and cold methanol precipitation. The purity of supernatant LPG (sLPG) and membrane LPG (mLPG) was determined by SDS-PAGE and thin layer chromatography. The effect of mLPG and sLPG on nitric oxide (NO) production by murine macrophages cell line (J774.1A) was studied. Both sLPG and mLPG induced NO production in a dose dependent manner but sLPG induced significantly higher amount of NO than mLPG. Our results show that sLPG is able to promote NO production by murine macrophages.